Strengths and Difficulties among Adolescent with and without Specific Learning Disorders (SLD) - Pikó Bettina; Dudok Réka (2023)
Specific Learning Disorders (SLD) have become a major concern in modern societies. It is essential to detect their emotional, behavioral and social consequences as early as childhood. The aim of this study is to examine a set of strengths and difficulties and compare them between students with and without SLD. Participants in this study were adolescents aged 11–18 years from Budapest and villages of its Metropolitan area (Hungary) (N = 276, mean age = 13.6 years, SD = 1.8, 54.7% boys). Due to multistage sampling, a nearly equal number of students had SLD or not. In addition to sociodemographics, the Strengths and Difficulties Questionnaire (SDQ), Satisfaction With Life Scale and the Proactive Coping Inventory were included in the survey, and t-test, correlation and logistic regression analysis were applied in statistical analyses. Our findings suggest that in early adolescence (ages 11–14 years), conduct and peer problems, in late adolescence (ages 15–18 years), emotional problems, highlighted SLD. In terms of strengths, prosocial behavior in children with SLD may compensate difficulties, especially at a younger age. Students from lower SES families and those having parents with a lower educational level are more likely to have a diagnosis of SLD. Teachers and special educators should take care of improving the adolescents’ prosociality, social and coping skills and listening to emotional, conduct and peer problems in those with SLD.
Keywords: Pszichológia